Euphemism roles as a disguise tool in political texts: A case study of Tempo online political articles - Jaganegara, Haidar; Wijana, I Dewa Putu (Program Studi Sastra Indonesia UIN Sunan Ampel Surabaya, 2023)
The mass media tends to use euphemisms in political news narratives. The euphemistic was chosen by the editor to avoid controversy due to the broadcast of a news material. This research aims to discuss the types of euphemisms in the news narrative on Tempo political articles (December 2022-January 2023). Political euphemism is seen through van Dijk's paradigm which focuses on local semantics and lexicon, especially how political leaders tend to use this style of language as a political linguistic tactic. The data in the form of political texts were then tested again with Allan and Burridge's concept of euphemism who thought that euphemism as an ideal style of language in social communication in order to achieve maximum effect to avoid sensitive topics. The results of the study conclude that there is a tendency to use euphemisms in word and phrase classes by politicians. Their linguistic corpus consists mostly of metaphors, synecdoche, borrowing, hyperbole, abbreviations, and acronyms.